2020
DOI: 10.1111/dme.14347
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors associated with HbA1c in adults with insulin pump‐treated type 1 diabetes: a systematic review

Abstract: Aims To identify currently available studies on the association between psychosocial factors and HbA 1c in adults with insulin pump-treated type 1 diabetes, by performing a systematic review of the literature. Methods MEDLINE, Embase, CINAHL and PsycINFO were searched for original studies on the association between psychosocial factors and HbA 1c in ≥ 50 adult, non-pregnant, insulin pump users with type 1 diabetes. Results The search resulted in 1777 unique records, of which eight were eligible for inclusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Studies have shown that management of T1D at optimal glycaemic levels can cause distress with constant blood glucose monitoring and concern over coping an acute hypoglycaemic event [39]. Positive associations between fear of hypoglycaemia and HbA1c have been demonstrated among those treated with insulin injections [40]. Conceptual words such as "management distress", "fear", and "worry", can be used to describe the anxiety and stress that people living with T1D might experience after their diabetes diagnosis (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that management of T1D at optimal glycaemic levels can cause distress with constant blood glucose monitoring and concern over coping an acute hypoglycaemic event [39]. Positive associations between fear of hypoglycaemia and HbA1c have been demonstrated among those treated with insulin injections [40]. Conceptual words such as "management distress", "fear", and "worry", can be used to describe the anxiety and stress that people living with T1D might experience after their diabetes diagnosis (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lower HbA1c levels relate to higher quality of life scores. The evidence regarding the associations between psychosocial factors and HbA1c levels among insulin pump users is however limited 16…”
Section: Introductionmentioning
confidence: 99%
“…Questionnaire content was informed by preceding works by the Steno Tech study group, including systematic literature reviews [ 19 , 20 , 33 ] and an interview study with insulin pump users [ 24 ] that explored possibilities and barriers to effective daily insulin pump management. The Steno Tech study group is an interdisciplinary collaboration of researchers and clinicians with extensive experience in type 1 diabetes and insulin pump treatment.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is currently no consensus on the best educational practice for a given patient [15,16], and there is a paucity of high-quality comparative studies regarding the effectiveness of insulin pump education [17][18][19]. Furthermore, psychosocial factors, such as self-efficacy, emotional (diabetes) distress and fear of hypoglycaemia, may also impact the use of technology and treatment outcomes, although the number of quantitative studies analysing the impact of these factors is limited [20,21]. Qualitative studies exploring how people live with an insulin pump suggest a variety of factors which may affect glucose levels and treatment satisfaction [22,23].…”
Section: Introductionmentioning
confidence: 99%